2016
DOI: 10.1039/c6ra20970j
|View full text |Cite
|
Sign up to set email alerts
|

Bromine substituted aminonaphthoquinones: synthesis, characterization, DFT and metal ion binding studies

Abstract: Bromine substituted aminonaphthoquinones – chemosensors for metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…As can be seen from Figure , the HOMOs of 3 b and 3 c are located over both moieties, mostly on the ‐NHR, Br groups and a lesser extent on the quinonoid skeleton ,. Any contribution of the quinonoid and Br fragments to the HOMO of 3 a was not observed in comparison with 3 b and 3 c .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…As can be seen from Figure , the HOMOs of 3 b and 3 c are located over both moieties, mostly on the ‐NHR, Br groups and a lesser extent on the quinonoid skeleton ,. Any contribution of the quinonoid and Br fragments to the HOMO of 3 a was not observed in comparison with 3 b and 3 c .…”
Section: Resultsmentioning
confidence: 90%
“…Both 3 c and 7 f crystallizes in a monoclinic space group P1 21/c1 which is typical for most of the quinone derivatives ,. Both crystals are strongly stabilized by π–π stacking interactions which can be easily realized from the packing motif figures and which is very common among 1,4‐naphthoquinone derivatives ,. Carbonyl bond distances of C1‐O1 of 1.214(8) Å and C8‐O2 of 1.225(6) Å in 3 c and C3‐O1 of 1.218(4)Å and C4‐O2 1.213(4)Å in 7 f are all in agreement with the naphthoquinone crystal structures found in the literature which are in their oxidized form ,,.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tetrahedral 1 : 1 complex Cu 2+ and 1 : 2 octahedral complex of Ni 2+ was proposed for such type of ligands. 40,41 Association constant of Cu 2+ ion was determined using the Stern-Volmer plots from uorescence experiments (Fig. S13 (for H-1) and Fig.…”
Section: Competitive Binding Ph Dependent Binding Studies and Detectmentioning
confidence: 99%
“…[62] In the present work, we investigate products resulting from the reactions of 2,3-dibromonaphthalene-1,4-dione and naphthalene-1,4-dione with pyridyl amines. The expected product in the reaction of 2,3-dibromonaphthalene-1,4-dione with (pyridine-2-yl)methanamine is 2-((pyridine-2-yl) methylamino)-3-bromonaphthalene-1,4-dione designated as 2MPA, [63] however, the reaction concomitantly leads to the formation of product 2-amino-3-bromonaphthalene-1,4-dione (A). It was further observed that the reaction of 2,3-dibromonaphthalene-1,4-dione with (pyridine-4-yl) methanamine yield the 2-aminonaphthalene-1,4-dione (B(1)).…”
Section: Introductionmentioning
confidence: 99%